Peningkatan Sifat Mekanis Kekerasan dan Impact Ductile Cast Iron FCD-50 Melalui Proses Heat Treatment dengan Pendinginan Oli - Weripih, Abdul Azis; Fadhillah, Arief Rizki; Suriansyah, Suriansyah (PROTON, 2023)
The demand for iron and steel metals in industry continues to increase, especially for cast iron applications such as gray, white, wrought and nodular cast iron (ductile cast iron). Ductile cast iron is widely used as a substitute for steel because of its mechanical properties that are close to steel, and has a high level of hardness. This study aims to determine the increase in hardness and impact properties of FCD-50 nodular cast iron through the heat treatment process. This method is done by heating the material at a certain temperature and cooling it using oil media. Hardness test and microstructure test were conducted as the main data analysis. The test results showed an increase in hardness from 54.2 HRC to 56.07 HRC. In addition, there was a change in the microstructure with the discovery of graphite, pearlite, and ferrite phases, where ferrite appeared more dominant and diffuse. These findings indicate that heat treatment is effective in improving the performance of ductile cast iron FCD-50.